2005
DOI: 10.1111/j.1745-6622.2005.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Pay Without Performance: Overview of the Issues

Abstract: In their recent book, "Pay Without Performance: The Unfulfilled Promise of Executive Compensation", the authors of this article provided a comprehensive critique of U.S. executive pay practices and the corporate governance processes that produce them, and then offered a number of proposals for improving both pay and governance. This article presents an overview of their analysis and proposals. 2005 Morgan Stanley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
230
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(243 citation statements)
references
References 18 publications
8
230
0
5
Order By: Relevance
“…Researcher showed that the level of executive compensation mainly depends on company properties as well as on personal characteristics of the manager. Firm size (Fahlenbrach 2009;Renner et al 2002) firm performance (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007), and a firm's ownership structure (Thomsen and Pedersen 2000;Chowdhury and Wang 2009) are company properties that researchers identified as drivers of executive compensation levels. Managers' tenure (Hill and Phan 1991) and gender (Kulich et al 2011;Renner et al 2002), on the other hand, are personal characteristics that influence managers' compensation levels directly or as moderating effects, e.g., through affecting labor market mobility and search firms' preferences (Dreher et al 2011).…”
Section: Literature Overview Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researcher showed that the level of executive compensation mainly depends on company properties as well as on personal characteristics of the manager. Firm size (Fahlenbrach 2009;Renner et al 2002) firm performance (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007), and a firm's ownership structure (Thomsen and Pedersen 2000;Chowdhury and Wang 2009) are company properties that researchers identified as drivers of executive compensation levels. Managers' tenure (Hill and Phan 1991) and gender (Kulich et al 2011;Renner et al 2002), on the other hand, are personal characteristics that influence managers' compensation levels directly or as moderating effects, e.g., through affecting labor market mobility and search firms' preferences (Dreher et al 2011).…”
Section: Literature Overview Theoretical Background and Hypothesesmentioning
confidence: 99%
“…As financial characteristics, we use LEVERAGE (quotient of total debt to total assets) as a proxy for the company's capital structure (Shaw and Zhang 2010) as well as the variable RISK (standard deviation of the operating performance over the focal and the 2 preceding years divided by their mean-winsorized to guard from outliers) to depict firm risk. We incorporate an accounting-based as well as a stock-based measure for firm performance (Kulich et al 2011;Adams and Ferreira 2009), i.e., the company's ROE and TOBIN'S Q, respectively, to control for their effects on executive compensation (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007).…”
Section: Variablesmentioning
confidence: 99%
“…The managerial power and managerial entrenchment literature suggests that the governance of corporate behavior may deviate from the normative perspective of agency theory (for an overview see Bebchuk & Fried, 2006). U.S.-based research indicates that some CEOs have been able to build a power base that weakens -or even isolates the CEO -from shareholder demands (Boyd, 1994;Zajac & Westphal, 1996).…”
Section: Dismissal Performance Sensitivitymentioning
confidence: 99%
“…However, for the economy as a whole, this is not the case. During the period 1993-2003, a total of six per cent of the net income of the firms in the USA was remitted to the top five executives of these firms (Bebchuk and Fried 2005). Furthermore, if payment failed to fully discipline the corporate elite as it is supposed to do, increased remuneration might be conceived of as a sign of the power position of corporate directors.…”
Section: Remuneration As Status Attainmentmentioning
confidence: 99%